A Non-enveloped Virus Hijacks Host Disaggregation Machinery to Translocate across the Endoplasmic Reticulum Membrane - Ravindran, Madhu Sudhan (PLoS Pathog, 2015)
Mammalian cytosolic Hsp110 family, in concert with the Hsc70:J-protein complex, functions as a disaggregation machinery to rectify protein misfolding problems. Here we uncover a novel role of this machinery in driving membrane translocation during viral entry. The non-enveloped virus SV40 penetrates the endoplasmic reticulum (ER) membrane to reach the cytosol, a critical infection step. Combining biochemical, cell-based, and imaging approaches, we find that the Hsp110 family member Hsp105 associates with the ER membrane J-protein B14. Here Hsp105 cooperates with Hsc70 and extracts the membrane-penetrating SV40 into the cytosol, potentially by disassembling the membrane-embedded virus. Hence the energy provided by the Hsc70-dependent Hsp105 disaggregation machinery can be harnessed to catalyze a membrane translocation event.